Sheep won't sleep - Cox, Judy, 1954-; Cuneo, Nina (New York : Holiday House, 2017)
A girl who cannot sleep decides to count sheep and other woolly animals by ones, twos, fives, and tens.
"Counting by 2s, 5s, and 10s"--Cover.
Keywords: Bedtime -- Juvenile fiction; Counting -- Juvenile fiction; Wool -- Juvenile fiction; Animals -- Juvenile fiction; Bedtime -- Fiction; Counting -- Fiction; Wool -- Fiction; Animals -- Fiction; Bedtime -- Fiction; Animals -- Fiction; Picture books; Counting -- Fiction; Wool -- Fiction; Fiction; Juvenile works; Picture books; Picture books